Unravelling the mechanism and significance of thrombin binding to platelet glycoprotein Ib - Ruggeri, Zaverio M.; Zarpellon, Alessandro; Roberts, James R.; Mc Clintock, Richard A.; Jing, Hua; Mendolicchio, G. Loredana (Thrombosis and Haemostasis, 2010)
The main question concerning the mechanism of α-thrombin binding to platelet membrane glycoprotein (GP)Ib is whether it involves both thrombin exosite I and exosite II. The solution of two independent crystal structures suggests alternative explanations that may actually reflect different modes of binding with distinct pathophysiological significance. With respect to function, it is still unclear whether thrombin binding to GPIb promotes procoagulant and prothrombotic pathways of re-sponse to vascular injury or limits such responses by sequestering, at least temporarily, the active enzyme. We review here published information on these topics and touch upon ongoing studies aimed at finding definitive answers to outstanding questions relevant for a better understanding of thrombosis and haemostasis.
Keywords: Thrombin; GPIb; von Willebrand factor; thrombosis; animal models